Dinâmica do ictioplâncton em um estuário tropical: Efeito dos filtros ambientais na distribuição espaço-temporal - Lima, Lidiane Gomes de (2018)
The connectivity between marine and freshwater environments enables estuaries to be important systems to numerous resident, marine and freshwater fish species that use these areas for feeding, protection, spawning and nursery. The constant fluctuations of environmental characteristics have direct influence on the composition, and distribution and abundance patterns of different organisms that inhabit these ecosystems, especially ichthyoplankton, whose patterns are shaped by biotic and abiotic factors that function as filters selecting the species along environmental gradients. Thus, this study aimed to determine the ichthyoplankton composition along the Mamanguape estuary, Paraíba, Brazil, evaluating its distribution and density in relation to the physical and chemical conditions of the environmental gradients towards the ocean. The samplings were carried out in three zones along the main channel, with horizontal subsurface trawls, and the environmental parameters were measured during the rainy and dry seasons in 2016. A total of 1,672 larvae and 486 eggs with higher densities were collected for the Engraulidae, Characidae, Clupeidae, Gerreidae, Mugilidae and Atherinopsidae families. The spatial-temporal variation was evident with the formation of distinct assemblages between the zones and the seasons, which were determined by the seasonal variation of salinity, pH, dissolved oxygen and temperature. During the rainy season, the highest densities were observed in the intermediate zone with the highest contribution of larvae in pre-flexion and flexion stages of the Engraulidae family and post-flexion larvae of the Clupeidae family. The greater fresh water intake in the estuary during the rainy season allowed the establishment of freshwater families such as the Characidae family in the uppermost estuary areas, as well as increasing pH values, making the environment conducive to development and settlement of larval assemblies. During the dry season, higher egg densities of Mugilidae, Engraulidae and Clupeidae families were recorded in the lower zone. The lower precipitation during this period allowed a greater saline intrusion to the upper zones of the estuary, allowing the establishment of exclusively marine families such as Sciaenidae and Bleniidae. These results highlight the importance of seasonal changes from fresh water discharge on salinity and the effect on other environmental variables to regulate the composition and distribution of ichthyoplankton in the Mamanguape estuary. In addition, the high abundance of larvae in the sac-yolk and pre-flexion stages indicates the use of the estuary as nursery.